The Role of Geographic Information System (GIS) in the Conservation of Cultural Heritage - Etlacakuş, Ayşen (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2025)
Cultural heritage is a fundamental component of the identity and collective memory of societies. However, population growth, unplanned development, climate change, natural disasters, and inadequate conservation efforts pose serious threats to its preservation. Sustainable conservation requires multi-component and interdisciplinary approaches. Geographic Information System (GIS) has emerged as effective tool for mapping, analyzing, conserving, and monitoring cultural heritage. This study aims to examine the role of GIS in the conservation-focused evaluation of cultural heritage elements at different scales, such as cultural landscapes and historical buildings. Case studies from various regions of Türkiye are analyzed to evaluate GIS contributions in tracking temporal changes through historical aerial photos, old and current maps, and land data; conducting integrity and authenticity analyses; and informing conservation strategies. The findings indicate that GIS supports interdisciplinary, holistic, and multi-dimensional approaches to cultural heritage conservation. This study intends to offer a methodological framework for future conservation-oriented research.